KECERDASAN BUATAN DAN KOMUNIKASI EFEKTIF: MENAVIGASI TANTANGAN DAN PELUANG DALAM BIMBINGAN KONSELING KONTEMPORER - Sulfikar K; Maslina; Fitriana, Fitriana (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2024)
This research explores the potential of artificial intelligence (AI)-based counseling in improving access and affordability of mental health services in Indonesia, especially in remote areas that lack trained professionals. By utilizing AI technology, counseling services can be accessed through mobile devices or computers, addressing gaps in existing mental health services. This research uses the literature study method. emphasizes the importance of AI system design that is able to customize counseling approaches. In addition, this research proposes an integrated counseling model between AI technology and local cultural values, involving collaboration between technology developers, traditional counselors, and local communities. With a comprehensive and culturally responsive approach, AI-based counseling can be an innovative solution to mental health challenges in Indonesia, while still respecting the nation's socio-cultural uniqueness. This research also recognizes that AI is not capable of replacing the role of humans, it can only be an auxiliary tool in the counseling process.